Deciphering the mode of action of a mutant Allium sativum Leaf Agglutinin (mASAL), a potent antifungal protein on Rhizoctonia solani. Issue 1 (December 2015) - Ghosh, Prithwi; Roy, Amit; Hess, Daniel; Ghosh, Anupama; Das, Sampa
Abstract Background MutantAllium sativum leaf agglutinin (mASAL) is a potent, biosafe, antifungal protein that exhibits fungicidal activity against different phytopathogenic fungi, includingRhizoctonia solani . Methods The effect of mASAL on the morphology ofR.solani was monitored primarily by scanning electron and light microscopic techniques. Besides different fluorescent probes were used for monitoring various intracellular changes associated with mASAL treatment like change in mitochondrial membrane potential (MMP), intracellular accumulation of reactive oxygen species (ROS) and induction of programmed cell death (PCD). In addition ligand blot followed by LC-MS/MS analyses were performed to detect the putative interactors of mASAL. Results Knowledge on the mode of function for any new protein is a prerequisite for its biotechnological application. Detailed morphological analysis of mASAL treatedR. solani hyphae using different microscopic techniques revealed a detrimental effect of mASAL on both the cell wall and the plasma membrane. Moreover, exposure to mASAL caused the loss of mitochondrial membrane potential (MMP) and the subsequent intracellular accumulation of reactive oxygen species (ROS) in the target organism. In conjunction with this observation, evidence of the induction of programmed cell death (PCD) was also noted in the mASAL treatedR. solani hyphae. Furthermore, we investigated its interacting partners fromR. solani . Using ligand blots followed by liquid chromatography tandem mass spectrometry (LC-MS/MS) analyses, we identified different binding partners including Actin, HSP70, ATPase and 14-3-3 protein. Conclusions Taken together, the present study provides insight into the probable mode of action of the antifungal protein, mASAL onR. solani which could be exploited in future biotechnological applications.